Literature Review: The Influence of Lecturer Competence on Effective Learning - Ida Rianti; Wanada Siti Salsabilah (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to review the influence of lecturer competence on the effectiveness of learning in higher education using a systematic literature review approach. Methodology: The methods used include a review of 10 recent articles that discuss aspects of lecturer competence, namely pedagogical, professional, social, technology adaptation, and inclusivity. Main Findings: The results of the analysis show that the pedagogical and professional competence of lecturers play a major role in supporting material understanding and student engagement. In addition, technological adaptation and inclusivity competencies are becoming increasingly important in the digital era and in dealing with diversity in the classroom. Lecturers' social competence was also found to support the creation of conducive interactions, which have a positive impact on learning effectiveness. Novelty/Originality of this study: The novelty of this study is a more comprehensive approach in reviewing the multifaceted role of lecturer competence, including aspects of technology and inclusivity, which have not been widely discussed in previous studies.